PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI ARITMATIKA SOSIAL DI KELAS VIIB SMPN 7 PALU: Application Of Cooperative Learning Model Type Two Stay Two Stray (Tsts) To Improve Students' Learning Outcomes On Social Arithmetics Material In Class Viib Smpn 7 Palu - Kadong, Ekslesya Evangelin; Idris, Mustamin; Hasbi, Muh. (Universitas Tadulako, 2024)
The purpose of this research is to describe the application of the Two Stay Two Stray (TSTS) type of cooperative learning model in the social aritmhmetic material which can improve the learning outcomes of VIIB grade students of SMPN 7 Palu. The research design refers to the design of Arikunto, which consists of 4 components, namely: (1) planning, (2) acting (3) observing and (4) reflection. The data collected is in the form of teacher and student activity data through observation sheets, interview results, and field notes. This research was conducted in two cycles totaling 18 students. The results showed that the application of the cooperative learning model type TSTS can improve the learning outcomes in the social arithmetic material in class VIIB students of SMPN 7 Palu by following the steps as follows: (1) preparation for learning, (2) conveying information, (3) organizing students into cooperative groups, (4) thinking together, (5) evaluating, (6) giving awards.